A comparison between Yfiler® and RM Y-STRs in United Arab Emirates population. (December 2015) - Alghafri, R.; Alhammadi, S.; Amiri, K.
Abstract: Rapidly Mutating Y-STRs (RM Y-STR) were proven to have significantly higher resolution in worldwide populations when compared to commonly used Y-STR kits. In order to contribute to the research that has been conducted so far, RM Y-STRs were investigated in parallel with Yfiler ® kit in 327 male individuals from United Arab Emirates population. Such population is considerably isolated where Yfiler ® and Powerplex ® Y haplotypes were found to be shared between distantly related as well as non-related male individuals. In the present study, a comparison between Y-STR markers included in Yfiler ® kit (DYS456, DYS389I, DYS390, DYS389II, DYS458, DYS19, DYS385, DYS393, DYS391, DYS439, DYS635, DYS392, YGATAH4, DYS437, DYS438, DYS448) with RM Y-STRs (DYF387S1, DYF399S1, DYF403S1a/b, DYF404S1, DYS449, DYS518, DYS526a/b, DYS547, DYS570, DYS576, DYS612, DYS626, and DYS627) is conducted. RM Y-STRs were analysed using previously published methods. Forensic parameters were calculated for each set of markers, including discrimination capacity, haplotype diversity and gene diversity, using Arlequin v3.5 software.